Molecular analyses of the LRRK2 gene in European and North African autosomal dominant Parkinson's disease. Issue 7 (8th April 2009) - Lesage, S; Condroyer, C; Lannuzel, A; Lohmann, E; Troiano, A; Tison, F; Damier, P; Thobois, S; Ouvrard-Hernandez, A-M; Rivaud-Péchoux, S; Brefel-Courbon, C; Destée, A; et al.
Abstract : Background: Mutations in the leucine-rich-repeat kinase 2 ( LRRK2 ) gene have been identified in families with autosomal dominant Parkinson's disease (ADPD), the most common of which is the p.G2019S substitution that has been found at varying frequencies worldwide. Because of the size of the LRRK2 gene, few studies have analysed the entire gene in large series of ADPD families. Methods: We performed extensive mutation analyses of all 51 coding exons of the LRRK2 gene in index cases from 226 Parkinson's disease families compatible with autosomal dominant inheritance, mostly from France (n = 182) and North Africa (n = 14). Results: We found 79 sequence variants, 29 of which were novel. Eight potentially or proven pathogenic mutations were found in 22 probands (9.7%). There were four novel amino acid substitutions that are potentially pathogenic (p.S52F, p.N363S, p.I810V, p.R1325Q) and two novel variants, p.H1216R and p.T1410M, that are probably not causative. The common p.G2019S mutation was identified in 13 probands (5.8%) including six from North Africa (43%). The known heterozygous p.R1441H and p.I1371V mutations were found in two probands each, and the p.E334K variant was identified in one single patient. Most potentially or proven pathogenic mutations were located in the functional domains of the Lrrk2 protein. Conclusion: This study leads us to conclude that LRRK2 mutations are a common cause of autosomal dominant Parkinson's disease in Europe and North Africa.